A novel web-based dynamic nomogram for recurrent laryngeal nerve lymph node metastasis in esophageal squamous cell carcinoma - Chen, Ting-Ting; Yan, Hao-Ji; He, Xi; Fu, Si-Yi; Zhang, Sheng-Xuan; Yang, Wan; Zuo, Yu-Jie; Tang, Hong-Tao; Yang, Jun-Jie; Liu, Pei-Zhi; Wen, Hong-Ying; Tian, Dong (Frontiers in Surgery, 2022)
Abstract Background Patients with esophageal squamous cell carcinoma (ESCC) are liable to develop recurrent laryngeal nerve (RLN) lymph node metastasis (LNM). We aimed to assess the predictive value of long diameter (LD) and short diameter (SD) of RLN lymph node (LN) and construct a web-based dynamic nomogram for RLN LNM prediction. Methods We reviewed 186 ESCC patients who underwent RLN LNs dissection from January 2016 to December 2018 in Affiliated Hospital of North Sichuan Medical College. Risk factors for left and right RLN LNM were determined by univariate and multivariate analysis. A web-based dynamic nomogram was constructed by using logistic regression. The performance was assessed by the area under the curve (AUC) and brier score. Models were internally validated by the five-fold cross-validation. Results Patients who underwent left and right RLN LN dissection were assigned into the left cohort (n = 132) and right cohort (n = 159), with RLN LNM rates of 15.9% (21/132) and 21.4% (34/159), respectively. The AUCs of LD (SD) of RLN LN were 0.663 (0.688) in the left cohort and 0.696 (0.705) in the right cohort. The multivariate analysis showed age, SD of RLN LN and clinical T stage were significant risk factors for left RLN LNM (all P < 0.05), while tumor location, SD of RLN LN and clinical T stage were significant risk factors for right RLN LNM (all P < 0.05). The dynamic nomograms showed reliable performance after five-fold cross-validation [(left (right), mean AUC: 0.814, range: 0.614-0.891 (0.775, range: 0.084-0.126); mean brier score: 0.103, range: 0.084-0.126 (0.145, range: 0.105-0.206)], available at https://mpthtw.shinyapps.io/leftnomo/ and https://mpthtw.shinyapps.io/rightnomo/. Conclusions LD and SD of RLN LN are inadequate to predict RLN LNM accurately, but online dynamic nomograms by combined risk factors show better prediction performance and convenient clinical application.